Formação continuada do coordenador pedagógico: o portfólio reflexivo como instrumento formativo - Barbosa, Liliane de Almeida (2020)
The research, linked to the Educational Management Research and Intervention Line (LIPIGES) of the Professional Master's Program in Management and Educational Practices (PROGEPE) at Nove de Julho University (UNINOVE), proposed as object of study the continuing education of the pedagogical coordinator , focusing on the reflective portfolio, developed by Casa do Professor (training center) of the Municipal Education Secretariat of Jandira, a city in the metropolitan region of São Paulo / SP. The questions that motivated and guided the development of the work: What is the conception of the coordinators about their own training process and of the teachers with whom they work? To what extent does the work carried out in the training carried out by Casa do Professor reach teachers? How does the education department monitor the coordinator's performance? How does the reflective portfolio contribute to the process of ongoing training for coordinators? The general objective was to consider the training of the pedagogical coordinator and its processes, as well as its relationship with the practice and its performance in the school unit. The following specific objectives were listed: (1) to understand how the pedagogical coordinator's continuing education takes place; (2) identify how the coordinator develops continuing education in service in his school unit; (3) constitute a training reference group; (4) reflect on the challenges and discuss changes in the continuing education of all those involved in the process. Research-training methodology with a qualitative approach; data collection, the reflective portfolio and electronic interview were adopted. The municipal education network in Jandira is considered a research universe and the subjects are two trainers from Casa do Professor (training center) and two pedagogical coordinators. Theoretical foundation supported by the authors: Garcia; Nóvoa; Canário; Almeida; Souza; Placco; Sá-Chaves; Josso and educational documents related to ongoing training, pedagogical coordination and reflection on practice. The results obtained indicate the relevance of the continuing education of the pedagogical coordinator based on reflection, considering a path that contemplates the mapping of the training needs, planning, development and monitoring of the participants and that the possibility of experiencing the reflective process allows to appropriate and so develop with their respective groups once they understand the benefits of this practice for improving the quality of teaching.